Особливості генеративного розмноження Aglaonema commutatum Schott (Araceae Juss.) при інтродукції - Ivanytska, B.O.; Zhila, A.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The results of the study of natural habitat conditions Aglaonema commutatum Schott (Araceae Juss.) are given. It is determined that the fruits of A. commutatum are heterokarpous and seeds are heterospermous and polyembryonous. The special feature of A. commutatum seed germination is emergence of 3–6 leaves (cataphyll) before additional root growth. Deficiency of embryonic root seedlings of A. commutatum would be considered as extreme ephemeral feature in monocotyledonous.